2005
DOI: 10.1111/j.0956-7976.2005.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Consuming Now or Later?

Abstract: Decisions are often temporally separated from their outcomes. Using theories of structural alignment and temporal construal, we examined how temporal distance and the associated shift in decision processes moderate susceptibility to context effects. Specifically, in two experiments (one hypothetical, one with real outcomes), we demonstrated that people attend more to nonalignable differences when the outcome of the decision is in the distant future than when it is in the near future. This shift in decision pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 35 publications
0
50
0
1
Order By: Relevance
“…A growing body of research on CLT has emphasized the benefits of thinking more abstractly and how “seeing the forest helps avoid getting tangled in the trees” (Henderson & Trope, , p. 402). For example, an abstract mindset has been shown to enhance creativity (Lile, Hirt, & Karpen, ), increase self‐control success (Fujita & Sasota, ), and it has been suggested that higher level construal may reduce a large variety of context biases (Malkoc, Zauberman, & Ulu, ). Yet, research has also revealed that higher level construal impedes performance at solving analytical problems (Förster, Friedman, & Liberman, ; Experiment 6), increases framing biases (McElroy & Mascari, ), and even undermines self‐control when an external stimulus activates a goal (Schmeichel, Vohs, & Duke, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research on CLT has emphasized the benefits of thinking more abstractly and how “seeing the forest helps avoid getting tangled in the trees” (Henderson & Trope, , p. 402). For example, an abstract mindset has been shown to enhance creativity (Lile, Hirt, & Karpen, ), increase self‐control success (Fujita & Sasota, ), and it has been suggested that higher level construal may reduce a large variety of context biases (Malkoc, Zauberman, & Ulu, ). Yet, research has also revealed that higher level construal impedes performance at solving analytical problems (Förster, Friedman, & Liberman, ; Experiment 6), increases framing biases (McElroy & Mascari, ), and even undermines self‐control when an external stimulus activates a goal (Schmeichel, Vohs, & Duke, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, love is more highly associated with higher level construal and global processing while lust is more highly associated with lower level construal and more analytic processing (Förster, Epstude, & Özelsel, ). Further, although higher level construal is commonly associated with improving the decision processes (e.g., Henderson & Trope, ; Malkoc, Zauberman, & Ulu, ), research has also demonstrated that lower level construal can have a positive impact on decision outcomes. For example, McElroy and Mascari () showed that considering an event in the near future triggered analytical thinking that reduced framing biases.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For high‐construal consumers, we would expect that messages communicating how well the extension fits with the parent brand, along with other abstract or generalized information (e.g., quality awards, the Good Housekeeping seal), would be more persuasive than messages describing specific attributes and usage contexts. In contrast, for low‐construal consumers, we would expect messages focusing on more specific and contextual information, such as detailed information (e.g., length of warranty) or attribute‐aligned comparisons to other brands (Malkoc, Zauberman, & Ulu, 2005), would be more persuasive.…”
Section: Conceptual Backgroundmentioning
confidence: 94%
“…On the basis of this argument, Malkoc, Zauberman, and Ulu (2005) reasoned that decisions that have distant future consequences (relative to near future consequences) would involve an increased consideration of nonalignable attributes. In a test of this prediction, participants evaluated two brands of potato chips and selected one brand to receive either at the end of the session (near future) or at the end of the semester (distant future).…”
Section: Basic Assumptions Of Cltmentioning
confidence: 99%